Constructing a diversified online neurology teaching model under the COVID-19 - Yang, Haojun; Fan, Yishu; Chen, Zhuohui; Zhang, Shiyu; Wu, Haiyue; Hu, Xinhang; Wu, Tong; Zhang, Mengqi (Frontiers in Medicine, 2023)
Purpose: To construct a diversified and comprehensive neurology network teaching model to provide highly qualified medical teaching under COVID-19 pandemic. Materials and Methods: We searched the published paper in Pubmed, Ebase, Cochrane and Medline related to this topic. By reviewing and summarizing available data, we constructed a specific online neurology teaching model and applied it to real scene. Besides, we designed and assigned questionnaires to get the feedback from students and improved this model according to their suggestions. Results: By combining advantages of modern information technology, scientific research, and online teaching, our newly constructed teaching model is proved to be a success and has received recognition from teachers and students. Conclusion: With the rapid development of technology, traditional single-mode teaching can no longer meet the needs of current medical education, especially under the rampant epidemic. This novel teaching mode, which orchestrate high-tech tools, diverse teaching methods and traditional teaching concepts, provides the solution to the challenge faced by traditional medical education. We believe that this diversified online teaching mode will boost neurology education and inspire educators in other fields during this tough period.